Identifying Perceived Barriers to Human Papillomavirus Vaccination as a Preventative Strategy for Cervical Cancer in Nigeria. Issue 1 (17th September 2020) - Nguyen, Nicole Yvonne; Okeke, Emeka; Anglemyer, Andrew; Brock, Tina
Background: Cervical cancer deaths are disproportionately higher in developing countries depicting one of the most profound health disparities existing today and is ranked as the second most frequent cancer among women in Nigeria. The Human Papillomavirus (HPV) vaccine as a primary prevention strategy is not widely used in Nigeria. This study investigated perceived barriers to HPV vaccination in a Nigerian community, targeting health workers' perceptions. Methods: This descriptive study captured responses from a cross-sectional, convenience sample of adult health workers within Anambra State, Nigeria. An anonymous 42-item survey with multiple validated scales was developed based on the Theory of Planned Behavior model and previous studies. The self-administered survey was distributed by research assistants at study sites within Anambra State which were identified through local constituents by the regional zones Adazi-Ani, Onitsha, and Awka. Data analyses were performed using Microsoft Excel for descriptive statistics and R software for the logistic regression, with a statistical significance level of 5%. Subgroup analysis was performed for the baseline knowledge questionnaire to determine if there were any differences in correct responses based on demographics such as: Institution type, profession, age, sex, religion and parental status. Results: Responses were collected from 137 Nigerian health workers; 44% nurses, 14% physicians, 6% pharmacists and 31% other health workers. The majority of respondents were female (69%), between 18 and 39 years of age (78%), from urban settings (82%), and identified as having Christian religious beliefs (97%). The most significant barriers identified were lack of awareness (39%), vaccine availability (39%), and cost (13%). When asked baseline knowledge questions regarding HPV, females were more likely to answer incorrectly as compared to males. Significant differences were found for statements: (1) HPV is sexually transmitted (p = 0.008) and (2) HPV is an infection that only affects women (p = 0.004). Conclusions: Perceived barriers to HPV vaccination identified by Nigerian health workers include lack of awareness, vaccine availability/accessibility, cost, and concerns about acceptability. Ongoing efforts to subsidize vaccine costs, campaigns to increase awareness of HPV vaccine, and interventions to improve attainability could advance administration rates in Nigeria, and ultimately improve death rates due to cervical cancer in this population.